Power decline and the change of self-esteem: The moderating effect of self-defense - Huang, Caiyun (Frontiers in Psychology, 2022)
Power is a fundamental force in social relationships. Having more power means more freedom and resources and the ability to control and influence others. Psychologically, people are afraid of power decline, therefore are motivated towards self-enhancement to avoid the decline of self-esteem. We asked if power decline brings about a subsequent decline in self-esteem. Objective: To investigate whether power decline in social relationships leads to a decline in self-esteem and to explore the moderating role of self-defense. Methods: A laboratory experiment was conducted with college students in East China as subjects, which was divided into manipulation tests of power decline and Self-Defense (N=61) and two formal experiments (N=65; N =160). In addition, a semi-structured in-depth interview was used to further improve the ecological validity of the findings. Results: ①power decline did not lead to a decline of self-esteem, and self-esteem rises when power remained unchanged; ②When the level of self-defense was higher, constant power lead to a greater increase of self-esteem, and the decline of power would not lead to the change of self-esteem; ③When the level of self-defense was lower, the relationship between constant power and the rise of self-esteem was weakened, and power decline would not lead to the significant change of self-esteem. At the end of this study, the theoretical and practical implications are discussed.